NLRC5 Inhibits Inflammation of Secretory Phase Ectopic Endometrial Stromal Cells by Up-Regulating Autophagy in Ovarian Endometriosis - He, Runhua; Liu, Xiaojing; Zhang, Jing; Wang, Zhongzheng; Wang, Wenyan; Fu, Liutao; Fan, Yijun; Sun, Shiying; Cao, Yunxia; Zhan, Lei; Shui, Lijun (Frontiers in Pharmacology, 2020)
Nod-like receptor (NLR) family caspase activation and recruitment domain containing 5 (NLRC5) is a newly identified sub-class of the NLR family. It regulates inflammation and has a key function in innate and adaptive immunologic reactions. Autophagy has been reported to be crucially linked to the pathogenesis of endometriosis. Our recent study identify there is a negative correlation between NLRC5 and autophagy in endometriosis, indicating that NLRC5 and autophagy together act as promising predictors in endometriosis patients. However, the mechanism associating NLRC5 and autophagy in endometriosis is still not completely understood. We hypothesize that autophagy could be involved in NLRC5-mediated inflammation in endometriosis. In order to validate the assumption, we evaluate the effects of NLRC5 and autophagy in the inflammation of ectopic endometrial stromal cells (EESCs) of ovarian endometriosis patients, to specifically determine whether autophagy is involved in NLRC5-mediated inflammation in EESCs. Our results show that over-expression of NLRC5 results in the up-regulation of autophagy in EESCs and inhibition of NLRC5 restricts the level of autophagy in EESCs. Furthermore, over-expression of NLRC5 and promotion of autophagy inhibit interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) expressions, whereas inhibition of NLRC5 and autophagy up-regulate IL-6 and TNF-α expressions in EESCs. Additionally, promotion of autophagy contributes to the NLRC5-mediated inhibition of IL-6 and TNF-α expressions in EESCs; inhibition of autophagy restricts NLRC5-mediated inhibition of IL-6 and TNF-α expressions in EESCs. Our results suggest that over-expression of NLRC5 promotes autophagy, thereby inhibiting inflammation in ovarian endometriosis.